Epidemiological review of spinal cord injury due to road traffic accidents in latin america (2021)
Spinal cord injury (SCI) is a disease that affects the normal function of the spinal cord. Road traffic accidents (RTAs) represent the main cause of SCI worldwide. SCI may generate physical disability and economic dependency, which is especially significant in low- and middle-income countries such as most of the Latin American countries. The main objective of this study was to present an epidemiological review of SCI secondary to RTAs. Stronger evidence on this condition in Latin America is important for future-specific data collection and prevention strategies. A literature review was carried out using specific search strategies in databases of indexed journals from the period 2000 to 2019. Data on SCI secondary to RTAs in the Latin American region were collected and analyzed. After initial screening and removal of duplicates, 16 articles met the inclusion criteria and were chosen for analysis. Data from 7 Latin American countries were retrievable. On average, RTAs were responsible for 40.81% of SCI. Data from different studies are heterogeneous. Car accidents and moto accidents were equally responsible for SCIs (50.61% vs. 49.06%). The thoracic segments were the most commonly affected (57.87%). Males in their 30s were the most affected category (76.6%). SCI due to RTAs may represent a severe but preventable condition that affects mostly men in their productive age, generating important social and economic issues. Data about this condition in Latin America are scarce, and could limit prevention and treatment strategies. Prospective data collection about this condition is recommended.